Effects of Self-Care on Quality of Life in Adults With Heart Failure and Their Spousal Caregivers: Testing Dyadic Dynamics Using the Actor–Partner Interdependence Model. (February 2014) - Vellone, Ercole; Chung, Misook L.; Cocchieri, Antonello; Rocco, Gennaro; Alvaro, Rosaria; Riegel, Barbara
Emotions are contagious in couples. The purpose of this study was to analyze the manner in which adults with chronic heart failure (HF) and their informal caregivers influence each other's self-care behavior and quality of life (QOL). A sample of 138 HF patients and spouses was enrolled from ambulatory centers across Italy. The Actor–Partner Interdependence Model (APIM) was used to analyze dyadic data obtained with the Self-Care of Heart Failure Index (SCHFI), the Caregivers Contribution to the SCHFI, and the Short Form 12. Both actor and partner effects were found. Higher self-care was related to lower physical QOL in patients and caregivers. Higher self-care maintenance in patients was associated with better mental QOL in caregivers. In caregivers, confidence in the ability to support patients in self-care was associated with improved caregivers' mental QOL, but worsened physical QOL in patients. Interventions that build the caregivers' confidence are needed.